Environmental footprint of windshield manufacture in Mexico - Ramírez-Díaz, Maritza Guadalupe; Patiño Pineda, José Arturo; Cortés Escobedo, Claudia Alicia (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2022)
Results of the life cycle analysis are presented for the calculation of the environmental footprint of the manufacture of a windshield in Mexico, considering different categories of impact, comparing its obtaining from raw materials extracted directly from nature, from recycling of glass and with the use of raw materials of mixed origin, with 23.5% recycled glass. The inventory data analyzed using the Simapro software showed a greater contribution to the potential environmental impacts corresponding to the transportation stage in all cases, in global warming and terrestrial ecotoxicity. The raw material with the greatest impact contribution is polyvinyl chloride, mainly in the depletion of stratospheric ozone and scarcity of fossil sources.